Increasing Company Value Through Internal and External Factors of the Company with Dividend Policy as a Moderating Variable - Salsabillah Akustika; Ira Wikartika (Indonesian Journal of Business Analytics, 2023)
This study aims to test whether company value can be influenced by institutional ownership, leverage, tax avoidance and using dividend policy as a moderating variable in LQ45 index companies for the 2019-2022 period. Based on purposive sampling there are 18 companies to be tested. Data testing uses the moderation regression test (MRA) method with SPSS. The results showed that there was a partial positive significant effect on institutional ownership also leverage on company value. While tax avoidance is significantly negative on company value. dividend policy can moderate the effect of institutional ownership and leverage on firm value, but is incapable of moderating the effect of tax avoidance on firm value.